Challenges associated with the identification of germline variants on myeloid malignancy genomic profiling—a Singaporean experience - Chin, Hui-Lin; Lam, Joyce Ching Mei; Christopher, Dheepa; Michelle, Poon Limei; Junrong, Benedict Yan (Frontiers in Oncology, 2023)
Genomic profiling to identify myeloid malignancy-related gene mutations is routinely performed for patients with suspected or definite myeloid malignancies. The most common specimen types in our experience are peripheral blood and bone marrow aspirates. Although primarily intended to identify somatic mutations, not infrequently, potentially clinically significant germline variants are also identified. Confirmation of the germline status of these variants is typically performed by hair follicle or skin fibroblast testing. If the germline variant is classified as a Pathogenic or Likely Pathogenic variant and occurs in a gene known to be associated with a disease relevant to the patient's phenotype (for example, the identification of a DDX41 pathogenic variant in an individual with acute myeloid leukemia), the management algorithm is typically quite straightforward. Challenging situations may occur such as when the germline variant is classified as a Pathogenic or Likely Pathogenic variant and occurs in a gene NOT known to be associated with the patient's phenotype/presenting complaint. We have encountered several such challenging cases in which potentially clinically significant germline variants were identified on the initial genomic profiling of peripheral blood or bone marrow aspirate. In this article, we present these cases, and discuss the genetic counseling and management approaches.